CRIMINAL TRIAL IN FRONT OF THE ROMAN SENATE DURING THE REIGN OF TIBERIUS (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The changes in the social-economic and state structure of Rome, carriedout at the time of the Principal (1st century BC – 3rd century AD), i.e. at thetransition from republican to monarchial state order, inevitably reflectedon the Roman criminal justice. Indeed, at this initial time of the so-calledRoman classical law, the remains of the former cognition procedure stillexisted and dominated the so-called Quaestiones perpetuae orQuaestiones ordinariae (jury courts), but, despite this, in the early periodof the Empire, new forms of criminal courts were introduced. In this paper,due to the limited available space, we will focus mainly on organizationand jurisdiction of the Roman Senate – as aristocratic state body of thenobility, and the trials that took place in front of it in this turbulent periodof Roman state and legal history, with particular regard to the rule of thesecond emperor Tiberius (ruled 14–37 AD).